Simulação e avaliação de incisões cirúrgicas com realidade virtual - Moura, Ives Fernando Martins Santos de (2017)
Incisions are a common task in most surgical procedures. Their learning is traditionally done in universities or teaching centers with the use of synthetic materials, animal parts, or, in more advanced stages, in real patients under the supervision of professionals. The use of simulators can contribute in this context of training, since with them it is possible to realistically simulate the materials used, carry out the practice repeatedly and immediately and automatically assess students' performance. Simulators capable of providing evaluation for the incision made in a given procedure are not common, and even those that exist do not have a specific assessment system for this task. The present study aimed to propose and develop an assessment system for surgical incisions simulated with computational methods, identifying the basic components of this process and using appropriate decision models for each of them. For this, the concepts and variables related to this procedure were studied, highlighting their most relevant characteristics and looking for ways to better provide assessment for them. The developed system considers two steps for the assessment of the incision, pre-surgical and surgical. The classical logic was the decision model used for most of the variables, with specific rules to deal with the particularities of each one. In order to evaluate the incision trajectory, the Support Vector Machine model was selected after experiments that compared the accuracy of the assessment of different decision models applied to databases containing rectilinear incision paths. For the validation of the system, metrics for the submental incision, component of the mandibular reconstruction procedure, used in the treatment of mandibular symphysis fractures, which has high prevalence in Brazil and in the world, were obtained and applied in an incision simulation in this region of the body. A computational incision simulation, the conceptualization of the evaluation system, a concrete implementation applied to the problem of the submental incision and conceptual maps, which systematize the knowledge used from different points of view, were produced in this work. It was verified that the assessment system responded adequately, with the classical logic rules and the Support Vector Machine providing results in accordance with the metrics used. Thus, it is observed that the assessment system proposed in this work represents an adequate tool for the use in the training of incision techniques.